Karakteristik fotosintesis dan produksi kedelai (Glycine max l. Merrill) akibat salinitas air penyiraman yang berbeda - Ria Safitri; Eny Fuskhah; Karno Karno (Journal of Agro Complex, 2018)
The aim of this research was to determine the effect of water saliny of watering up to 6 mmhos/cm on the characteristic of photosynthesis and soybean (Glycine max L. Merrill) production. The experiment was conducted in research field and Ecology and Plant Production Laboratory and Physiology and Breeding Plant Laboratory, Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang. The research method was a randomized block design with 6 treatments and 4 replications. The treatments were L0 = watering using fresh water (control), L1 = watering water saline with EC 2 mmhos/cm, L2 = watering water saline with EC 3 mmhos/cm, L3 = watering saline water with EC 4 mmhos/cm, L4 = watering saline water with EC 5 mmhos/cm, L5 = watering water saline with EC 6 mmhos/cm. The parameters observed were chlorophyll index, total leaf area, Net Assimilation Rate (LAB), leaf weight, stem weight, leaf and stem ratio, dry matter/100 seed, seed production/plot. The results showed that the watering treatment of up to 6 mmhos/cm had no significant effect on all parameters observed. Keywords: watering, salinity, photosynthesis, production, soybean.